Prediction of rainfall using data mining techniques - Prema, Fahmida Tasnim; Ahmed, Sharmin; Islam, Md. Rifat (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.